The Role of Teachers in Moral Education through the Habitus Model - Katni, Katni; Pramesty, Erinda Setya; Tajab, Muh (Universitas Muhammadiyah Magelang, 2025)
Moral crises continue to affect both educational and governmental institutions in Indonesia, undermining students’ moral development and damaging institutional reputations. In contrast, teachers at State Vocational High School 2 Pacitan have played a significant role in fostering commendable moral values, thereby reducing instances of immoral behavior. This study aims to analyze the role of teachers in moral education and identify the steps involved in promoting commendable character at the school. A descriptive qualitative approach was employed, involving interviews with the principal, vice principal, and students, as well as observations and document analysis. Data were analyzed through description, classification, interpretation, and theorization. The findings highlight that teacher act as facilitators, motivators, and role models by integrating knowledge, practice, habituation, advice, motivation, personal guidance, and religious activities. These practices were conceptualized into a “habitus model” of moral education, derived from Pierre Bourdieu’s sociological theory of habitus. This model emphasizes the formation of moral dispositions through consistent experience and interaction within the school environment. Key aspects include fostering value awareness, shaping behavioral dispositions, and promoting consistent moral practice. The model is operationalized through the 5M steps: knowing the good, habituating the good, loving the good, desiring the good, and doing the good.